Increasing Public Knowledge Regarding Beyond Use Date (Bud) In Dusun Mangir Tengah, Sendangsari, Bantul - Wulandari, Ari Susiana; Nurinda, Eva; Fatmawati, Annisa; Sarwadhamana, Raden Jaka; Putri, Imram Radne Rimba; Mastamah, Mastamah; Nadia, Melta Ainun; Manusu, Abd Sukri S; Astuti, Eka Dyah Ayu; Septiandi, Baiq Husnul Hotima; Ariski, Denis; Sati, Eva Laras; Zendrato, Mei Albert; Adelia, Melina Freda; Asrori, Moh; Veronika, Nabela (TRANSFORMASI : JURNAL PENGABDIAN PADA MASYARAKAT, 2024)
Beyond Use Date (BUD) is the deadline for the use of drugs after they have been formulated or after the main cover has been opened. Meanwhile, the expiration date (ED) is the deadline for the use of drugs after they are produced by pharmaceutical factories and before the cover is opened. The purpose of this service activity is to provide knowledge to the people of Mangir Tengah Hamlet, Sendangsari, Bantul about the importance of proper drug storage. BUD determines how effectively the drug is used. This community service activity was carried out in March 2024 by the Alma Ata University Thematic KKN team in the hamlet of Mangir Tengah, Sendangsari, Pajangan, Bantul. The methods used were lectures, leaflet distribution, and pre-post-test methods in the form of questionnaires. Based on the results of the data analysis, it was shown that there was an increase in knowledge for 21 respondents after the intervention was given. In comparison, 4 others experienced a decrease in knowledge and 10 respondents had stag knowledge. The results of the Wilcoxon test showed that there was a significant difference in the level of community knowledge before and after the intervention was given, which was shown by a p-value of 0.003. This educational activity concluded that the knowledge of the people of Central Mangir Hamlet has increased and was useful.